PELATIHAN PEMANFAATAN DAUN SINGKONG MENJADI DENDENG BAGI KELOMPOK PENERIMA PROGRAM KELUARGA HARAPAN - Richard Andreas Sunardi; Utary Pramesti Rahayu; Momi Oktaviani Saputri; Qais Muhammad Ramdhani (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Darmacaang Village is one of the villages in Cikoneng District, Ciamis Regency. The location of this village is under the foot of Mount Sawal. Most of the area is used for agricultural land such as cassava plantations while the rest is for dry land, namely land for the construction of houses and other buildings. The cassava plant is looked down upon especially the leaves, most of which are thrown away and only given to livestock. Seeing the very high potential of cassava leaves in Darmacaang Village, Cikoneng District, Ciamis Regency became an incentive for PLP participants at the Ciamis District Social Service, Siliwangi University to carry out the Dendeng Training program from cassava leaves with the aim of providing understanding, reducing expenses, and being able to provide provision for the participants, namely KPM PKH, to develop further which will later develop into the characteristics of tourist souvenirs in Darmacaang Village.